2008
DOI: 10.1590/s1517-83822008000300021
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Arcobacter butzleri CCUG 30484 on plastic, stainless steel and glass surfaces

Abstract: The persistence of A. butzleri CCUG 30484 on various surfaces under 32% and 64% relative humidity suspended in physiological saline or nutrient broth to simulate relatively clean or soiled conditions was studied using various isolation techniques. Our study revealed that A. butzleri CCUG 30484 cells were able to survive for a considerable period of time, even after the droplet of suspending medium has been visibly dried. An extended survival on polypropylene coupons at both humidity levels was observed, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The results showed that the mean roughness of a material is not a proof of cleanability and hygienic quality. In 2008 Cervenka et al used a similar method on plastic and stainless steel to study the persistence of Arcobacter butzleri on these two surfaces (25 cm²) [40]. In this study, sonication was applied at 38 kHz for 5 minutes and the results proved that Arcobacter could survive for a long time on a surface with a low surface free energy like plastic compared to a higher surface free energy like metal.…”
Section: Destructive Recovery Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…The results showed that the mean roughness of a material is not a proof of cleanability and hygienic quality. In 2008 Cervenka et al used a similar method on plastic and stainless steel to study the persistence of Arcobacter butzleri on these two surfaces (25 cm²) [40]. In this study, sonication was applied at 38 kHz for 5 minutes and the results proved that Arcobacter could survive for a long time on a surface with a low surface free energy like plastic compared to a higher surface free energy like metal.…”
Section: Destructive Recovery Methodsmentioning
confidence: 76%
“…Cervenka et al described a “coupon-printing method” which was tested only in the laboratory. Stainless steel, polypropylene and glass 1.5 × 1.5 cm chips were put on a selective agar medium for 5 minutes then aseptically recovered in order to incubate the plates and observe the viable cells [40]. The results were used to compare the persistence of bacteria on three surfaces and it was concluded that Arcobacter butzleri was more persistent on plastic.…”
Section: Non-destructive Recovery Methodsmentioning
confidence: 99%
“…Both characteristics have been described in some zoonotic food-borne pathogens like Listeria monocytogenes [10,21] and Yersinia enterocolitica [10,23]. In the case of Arcobacter butzleri, a few studies on attachment to inert surfaces [1,4,18] and in vitro adhesion to epithelial cells [3,11,22,28,29] are available.…”
Section: Discussionmentioning
confidence: 99%
“…First, A. butzleri adhere to HEp-2 cells and then, due to their capacity to form biofilms, interbacterial adherence can be expressed. Previous studies have demonstrated the capacity of A. butzleri to form biofilms while attaching to stainless steel, copper and glass [1,4,18].…”
Section: Discussionmentioning
confidence: 99%
“…Extended survival times have been reported for A. butzleri cells on polypropylene at high humidity, particularly in soiled conditions (Cervenka et al, 2008). Extended survival times have been reported for A. butzleri cells on polypropylene at high humidity, particularly in soiled conditions (Cervenka et al, 2008).…”
Section: Controlmentioning
confidence: 97%